Pengaruh Profitabilitas, Leverage, dan Sales Growth Terhadap Tax Avoidance di Era Pandemi Covid – 19 (Studi Kasus di Sektor Industri Barang Konsumsi yang Terdaftar di BEI) - Dewi Rinjani Amalia; Gunarianto Gunarianto; Irfan Fatoni (JPA : Journal of Public Accounting, 2022)
This study aims to find out empirically the factors that influence tax avoidance using the variables of profitability, leverage, and sales growth in consumer goods manufacturing companies listed on the Indonesia Stock Exchange in 2020. This type of research is a quantitative study using the purposive method. sampling. The data in this study were collected using the documentation method. The analytical method used in this study is multiple linear regression using the SPSS program. The type of data used in this study uses pooled data. The results of this study indicate that profitability, leverage, and sales growth have a negative and partially significant effect on tax avoidance, while profitability, leverage, and sales growth have a simultaneous positive and significant effect on tax avoidance.